PENGARUH STRUKTUR KEPEMILIKAN DAN FAKTOR LAINNYA TERHADAP PENGHINDARAN PAJAK - NOVANTIKO RAMADHAN; ARWINA KARMUDIANDRI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
This research aims to obtain empirical evidence on the influence of family ownership, institutional ownership, managerial ownership, and government ownership, profitability, leverage, and audit quality on Book Tax Difference (BTD). based on the premise that differences between accounting income and taxable income remain an important issue in corporate taxation and financial reporting practices. The object of this study is companies listed on the IDX, with a sample of 120 companies and a total of 435 observations selected using a purposive sampling method. The data used are secondary data obtained from companies’ annual financial statements and analyzed using multiple linear regression analysis with the assistance of SPSS version 25. The results indicate that all independent variables simultaneously have a significant effect on Book Tax Difference, while partially profitability and leverage have a positive and significant effect on BTD, whereas family ownership, institutional ownership, managerial ownership, government ownership, and audit quality have no significant effect. These findings suggest that firm financial factors play a more dominant role in influencing the difference between accounting income and taxable income than ownership structure.